2021
DOI: 10.1093/esr/jcab001
|View full text |Cite
|
Sign up to set email alerts
|

Spreading Uncertainty, Shrinking Birth Rates: A Natural Experiment for Italy

Abstract: Many previous studies have documented the procyclicality of fertility to business cycles or labour market indicators in Western countries. However, part of the recent fertility decline witnessed since the Great Recession has been left unexplained by traditional measures. The present study advances the notion that birth postponement might have accelerated in response to rising uncertainty, which fuelled negative expectations and declining levels of confidence about the future. To provide empirical support for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 69 publications
1
36
0
Order By: Relevance
“…Schneider (2015) suggested that press coverage of the economy can more accurately measure the sentiments that shape economic uncertainty and affect fertility behaviors than objective indicators such as unemployment and foreclosures. Comolli and Vignoli (2021) showed that the general public responds to the media's framing of uncertainty, with implications for childbearing. Interestingly, the results obtained within communication research suggest that negative news has a stronger impact on perceptions than positive reports.…”
Section: Narratives Of the Futurementioning
confidence: 99%
“…Schneider (2015) suggested that press coverage of the economy can more accurately measure the sentiments that shape economic uncertainty and affect fertility behaviors than objective indicators such as unemployment and foreclosures. Comolli and Vignoli (2021) showed that the general public responds to the media's framing of uncertainty, with implications for childbearing. Interestingly, the results obtained within communication research suggest that negative news has a stronger impact on perceptions than positive reports.…”
Section: Narratives Of the Futurementioning
confidence: 99%
“…And fertility tends to decrease when economic conditions are less certain (Sobotka et al, 2011). The recent effects of the Great Recession amplified the importance of economic uncertainty for childbearing (Caltabiano et al, 2017;Comolli & Vignoli, 2021;Comolli, 2017;. Notably, while the effect of economic changes on fertility was found to be the strongest in countries most affected by the economic recession , financial and labour market uncertainty affects fertility decisions even in countries where basic material conditions are stable and the state is protective .…”
Section: Fertility Choices In the Pre-pandemic Eramentioning
confidence: 99%
“…However, past evidence on fertility responses to external shocks, such as economic crises and financial turbulences (Sobotka et al 2011;Comolli 2017) as well as on the outbreaks of infectious diseases such as the Zika infection in Latin America (Rangel et al 2020;Marteleto et al 2020) show that people often postpone or revise their childbearing plans in uncertain times (Vignoli et al 2020). These responses result in considerable short-term fluctuations in fertility (e.g., Comolli and Vignoli 2021). Indeed, surveys on fertility intentions in Europe and in the United States during the first wave of the COVID-19 pandemic in Spring 2020 revealed that many women decided to delay or even give up their childbearing plans (Lindberg et al 2020;Luppi et al 2020).…”
Section: Introductionmentioning
confidence: 99%